Subalternization and indigenous resistance: Scenarios from the context of the state of Rondônia - Rozane Alonso Alves; Maria Isabel Alonso Alves; Jonatha Daniel dos Santos (Arizona State University, 2020)
The central idea of this article is to problematize and present some scenarios of subalternization and indigenous resistance, specifically, in the State of Rondônia. We started from research developed in the context of Rondônia (Alves, 2017, 2018; Alves Santos, 2017; Scaramuzza, 2015, Santos, 2020, among others) to expose the strategies used by the indigenous peoples of Rondônia as a struggle and resistance of the indigenous communities, becoming protagonists in spaces of formation and school performance. Linked to protagonism, the indigenous school as an intercultural space, promotes pedagogical practices based on the curriculum that is not only effective due to the disciplinary contents, but also as a cosmological process that occurs through Indigenous Pedagogy produced not only by its teachers, but throughout organic structure of the community. Thus, we understand that the indigenous school as a space of resistance and indigenous struggle is constituted and presented as intercultural and produces ways of being specific to indigenous peoples.